Zmiany sytuacji mieszkaniowej w Polsce w latach 1950–2002 - Gorczyca, Mirosław (MITEL, 2004)
W artykule tym autor przedstawia problem mieszkaniowy w Polsce oraz fundamenowe sposoby ich rozwiązania. Opłaty za mieszkania w latach 1950–2002 zostały przeanalizowane według krajowych spisów mieszkaniowych: 1950, 1960, 1970, 1978, 1988 i 2002. W 2000 r. autor wyliczenia potrzeb w zakresie inwestycji mieszkaniowych w celu uzyskania średniego standardu mieszkaniowego krajów Unii Europejskiej.

In this paper the author presents the housing problem in Poland and the fundamental ways of solving them. Charges in housing situation in the period of 1950–2002 were analysed according to the National Housing Censuses: 1950, 1960, 1970, 1978, 1988 and 2002. The author carried out the calculation of needs in housing investment to obtain an average housing standard of European Union countries in 2000.
Changes in the Housing Situation in Poland in the Period of 1950–2002